The single nucleotide polymorphism g.1548A >G (K469E) of the ICAM-1 gene is associated with worse prognosis in non-small cell lung cancer. - Thanopoulou, Eirini; Kotzamanis, George; Pateras, Ioannis S; Ziras, Nicholaos; Papalambros, Alexandros; Mariolis-Sapsakos, Theodoros; Sigala, Fragiska; Johnson, Elizabeth; Kotsinas, Athanassios; Andreas Scorilas; Gorgoulis, Vassilis G (Tumour Biol, 2012)
Intercellular adhesion molecule-1 (ICAM-1), a cell adhesion molecule with a key role in inflammation and immunosurveillance, has been implicated in carcinogenesis by facilitating instability of the tumor environment. The K469E single nucleotide polymorphism (SNP) (G>A) affects the ICAM-1 mRNA splicing pattern; the alternatively spliced isoform (ICAM-1-S) lacks transmembrane and intracellular domain, which affects the structural and signal transduction properties. Moreover, the expression of ICAM-1 is transcriptionally regulated by p53, and this SNP has been shown to be related with apoptosis. PCR-RFLP analysis was used to assess the K469E SNP status comparatively in 203 non-small cell lung cancer patients and 175 healthy sex-matched controls. This SNP was examined in relation to tumor kinetic parameters (Ki-67 immunohistochemical evaluation and Tdt-mediated dUTP nick end labeling assay), p53 immunohistochemistry status, and clinicopathological data in patients with operable stages. Both the genotype and allele frequency did not differ significantly between patients and controls. However, patients with the AG/AA genotypes had worse survival (39 vs 45 months, p = 0.036) and tended to be present in advanced stages (p = 0.057). Moreover, the AG/AA genotypes exerted a synergistic effect with aberrant p53 on tumor progression, while the GG genotype retained a better apoptotic index. The AG/AA genotypes correlated with worse survival and advanced stages probably due to defective immunosurveillance and apoptosis. These genetic backgrounds may confer a selective advantage for dissemination of tumor cells with high metastatic potential compared to GG genotype.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Carcinoma, Non-Small-Cell Lung; Case-Control Studies; Disease Progression; Female; Gene Frequency; Genotype; Humans; Intercellular Adhesion Molecule-1; Lung Neoplasms; Male; Middle Aged; Neoplasm Staging; Polymorphism, Single Nucleotide; Prognosis; Tumor Suppressor Protein p53